The Role of Elections in Peacebuilding (Journal of human and social sciences, 2025)
Elections are considered one of the most effective means to achieve legitimate interests in situations of disagreement, conflict, and chaos. Such conditions can only be resolved through resorting to the ballot box, ensuring that all parties accept the choice of the people. Voting for the most suitable candidate is a moral and religious responsibility entrusted to citizens, aiming to select those who are most capable of bearing public responsibility. In the absence of ideal candidates, voters should choose the one closest to truth, goodness, and integrity, in order to minimize harm and prevent greater corruption with lesser harm. The study emphasizes that making positive and responsible electoral decisions can contribute significantly to national stability and peacebuilding.
Keywords: Elections; Islamic Jurisprudence; Interests and Harms; Political Participation; Representatives of the Community